2012
DOI: 10.1017/s0007114512000128
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of vitamin A in growing dogs

Abstract: The safe upper limit for inclusion of vitamin A in complete diets for growing dogs is uncertain, with the result that current recommendations range from 5.24 to 104.80 μmol retinol (5000 to 100 000 IU vitamin A)/4184 kJ (1000 kcal) metabolisable energy (ME). The aim of the present study was to determine the effect of feeding four concentrations of vitamin A to puppies from weaning until 1 year of age. A total of forty-nine puppies, of two breeds, Labrador Retriever and Miniature Schnauzer, were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…More recently, eight-week-old Labrador Retrievers and Miniature Schnauzers were fed one of four retinyl acetate concentrations to achieve intakes of 5.24, 13.10, 78.60, and 104.80 umol retinol (5000, 12 500, 75 000, and 100 000 IU VA/4184 kJ) (1000 kcal) ME for 1 yr [29]. There was no effect of VA concentration on any hematological or biochemical variables, bone-specific alkaline phosphatase, crossed-linked carboxyterminal telopeptides of type one collagen, and dual X-ray absorptiometry.…”
Section: Vitamin Amentioning
confidence: 99%
“…More recently, eight-week-old Labrador Retrievers and Miniature Schnauzers were fed one of four retinyl acetate concentrations to achieve intakes of 5.24, 13.10, 78.60, and 104.80 umol retinol (5000, 12 500, 75 000, and 100 000 IU VA/4184 kJ) (1000 kcal) ME for 1 yr [29]. There was no effect of VA concentration on any hematological or biochemical variables, bone-specific alkaline phosphatase, crossed-linked carboxyterminal telopeptides of type one collagen, and dual X-ray absorptiometry.…”
Section: Vitamin Amentioning
confidence: 99%
“…Data on the safety of dietary vitamin A intake at levels up to 104·80 μmol retinol (100 000 IU vitamin A)/4184 kJ (1000 kcal) have been reported previously with regard to the markers of vitamin A metabolism, haematological and biochemical variables and dual-energy X-ray absorptiometry ( 3 ) . In the present study, we evaluated the development of body weight and body composition and compared observed energy intake with predicted energy intake in response to the potential impact of dietary vitamin A intake.…”
mentioning
confidence: 98%
“…Vitamin A is an essential nutrient for dogs; however, intake of dietary vitamin A can be variable and is dependent on the natural levels of vitamin A found in some raw materials used in petfood, especially liver. Previously, it has been shown that growing as well as adult dogs can tolerate a wide range of vitamin A levels in their diet ( 1 – 3 ) due to their capacity to increase the levels of retinyl esters in serum ( 4 ) and the ability to excrete vitamin A as both retinol and retinyl esters in the urine ( 3 , 5 – 7 ) . The impact of vitamin A and its metabolic product retinoic acid on energy metabolism in dogs is not clear, although data from rodents indicate an influence of retinoic acid on both thermogenesis and lipid synthesis via its actions when bound to the retinoic acid receptor ( 7 , 8 ) .…”
mentioning
confidence: 99%
“…Moreover, the rice bran diet presented greater palatability compared to the defatted rice bran diet. Vitamin A (retinol), whose safe upper limit in complete diets for dogs ranges from 5.24 to 104.80 mmol, is an essential fat-soluble vitamin at the center of investigations in dogs in the context of immune stimulation, vision-supporting functions, reproduction, bone growth, and cellular differentiation [88][89][90]. In dogs, unlike humans where retinyl esters are only detected in plasma in cases of intoxication or following a vitamin A-rich meal [91], vitamin A is present in the plasma predominantly in the form of retinyl esters, in both adequate and vitamin A-deprived states [92].…”
Section: The "Market Stand" Of Functional Pet Foodsmentioning
confidence: 99%